Review: Possible removal of heavy metal and selective rare-earth ions by polymeric and nano-composite materials. - Hieu, Nguyen Duc; Xuan, Chu Thi; Thanh, Pham Duc; Tuan, Mai Anh (Vietnam Journal of Chemistry, 2016)
Heavy metal contamination in aqueous environment from natural processes and human’s activities including pesticides usage, mining, factories discharging and leaking irritation shows an extreme threat to environment and human health. The control of rising amount of heavy metal in environment not only requires critical observations at their original sources but also demands efficient removal methods. However, each conventional method is only suitable in a certain range of use. For example, inexpensive materials and convenient techniques are necessary for large scale heavy meal treatment, while high performance system to remove almost trace amount of heavy metals are critically required for drinking water treatment. On the other hands, heavy metal treatments must be applicable in some crucial environment conditions. Among solutions for environmental heavy metal control, polymeric materials have showed many advantages to enhance the performance of conventional heavy metal adsorbents. Possessing functional chemical moieties on their side chains and backbones, polymers can act as main metal ion adsorption component and/or effective supports for the adsorption property. In addition, the utilization of polymeric components can result in a low corrosion, selectivity, controllability, and recyclability of absorbents when operated in real environment conditions. This article summarizes the preparation techniques and desirable properties of polymer for removal of toxic heavy metal ion as well as the possibility of polymers in collecting some rare noble metal ions. Keywords. Heavy metal ions, nano-composite, polymer.